Clitoromegaly caused by ovarian stimulation in a preterm newborn: ovarian hyperstimulation syndrome of preterm babies - Bayramoğlu, Elvan; Erdeve, Şenay Savaş; Derinkuyu, Betül Emine; Çelik, İstemi Han and Çetinkaya, Semra and Aycan, Zehra (The Turkish Journal of Pediatrics, 2020)
Background. Preterm ovarian hyperstimulation syndrome (POHS) is an uncommon disorder characterized by prematurity, hypogastric and upper leg swelling, high serum estradiol and gonadotropin levels, and ovarian cysts. Immaturity of the gonadal axis is accepted as the cause. But still, other etiological factors are suspected. Case. A preterm baby who was born at 24 gestational weeks was referred to our clinic for ambiguous genitalia on day 118 of life. Labia majora and clitoris was edematous. Clitoris length was 1.5 cm. On laboratory evaluation: 17OH-Progesterone: 1.84 ng/ml, dehydroepiandrosterone sulphate (DHEA-S): 139 μg/dl, total testosterone (T.T): 88 ng/dl, luteinizing hormone (LH): 22.5 mIU/l, Follicle stimulating hormone (FSH): 15.7 mIU/l, estradiol (E2): 447 pg/ml. Karyotype analysis was 46, XX. There was a 25x14x12 mm ovarian cyst detected on ultrasound. On follow-up, E2 levels and cyst size increased, and there was 4 mm pericardial effusion on echocardiography at the time. Conclusion. In this paper, we present a case with POHS and to discuss possible pathophysiological mechanisms and treatment. This is the first case of POHS developing pericardial effusion.